Study of informal reasoning in judicial agents in sexual aggression cases - Camplá, Xaviera; Gancedo, Yurena; Sanmarco, Jéssica; Montes, Álvaro; Novo, Mercedes (Frontiers in Psychology, 2022)
BACKGROUND/OBJECTIVE: Judicial judgment making must rest on formal reasoning. Nevertheless, informal reasoning sources (cognitive and motivational biases) were observed in judicial judgment making. Literature has identified sexual aggression cases as the most favorable for informal reasoning. Thus, a field study was designed with the aim of assessing the incidence and effects of cognitive and motivational biases in judicial agents in a case to rape to a woman. METHOD: As for this, an allegation (weak evidence) of female sexual aggression, manipulating two conditions (known perpetrator vs. unknown perpetrator), was presented for assessment to 217 Chilean judicial agents (76 enforcement officers, 60 correction officers, 67 prosecutors and 14 judges). The judicial agents answered to a measure of the myths about sexual aggression, the attribution of responsibility to complainant, the attribution of responsibility to accused, the attribution of credibility to the complainant testimony, the attribution of a nature of a rape to the alleged facts and an estimation of the probability of false/unfounded accusations. RESULTS: The results revealed an estimation of false/unfounded accusations of sexual aggression significantly higher than the mean of the best estimates, but into the upper limit of the best estimates; that the studied population did not share, in general, the myths about sexual aggression; and that the sources of attributional biases were driven in favor and against the complainant. Nevertheless, the case study showed that a large number of judicial agents participated of an overestimation of the probabilities of false or unfounded allegations; of the myths about sexual aggressions and of attributional biases against the complainant. CONCLUSIONS: In conclusion, informal reasoning sources were observed in judicial agents when only formal reasoning should prevail. Thus, judicial agents should be trained to control these sources of bias substituting them by formal reasoning (evidence).